Governance, Innovation, and Sustainable Development (Journey for Sustainable Development and Peace Journal, 2023)
The role of good governance and innovation is critical in ensuring a favorable investment environment and sustainable development. A review of the literature suggests that there is an affirmative relationship between governance, innovation, and sustainable development directly or indirectly. Without governance, innovation and sustainability could not go ahead smoothly, and the same in light of innovation. Good governance is crucial for tackling any kind of challenges regarding development. At the same, innovative technology enhances governance and sustainable development.